Robotic fish scales driven by a skin muscle mechanism. (June 2022) - Wang, Jieyu; Xi, Fengfeng
Highlights: This paper proposes a robotic fish scale driven by a muscle mechanism. The 4R and 5R linkages are combined to form a 1-DOF mechanism. The mechanism is loop-coupled with multiple tracer points. The tracer points of the mechanism can follow three desired curves. There is no interference and gap between the scales. Abstract: This paper proposes a robotic fish scale that serves as a cover driven by a muscle mechanism. A combinatory design method is put forward to design the underlying mechanism and the cover enclosing it for shape morphing. The muscle mechanism is bio-inspired to mimic the motion of the skin muscle. It is designed to consist of multi-loop linkages to serve as a driving skin muscle. The tracer points of the linkages are required to follow three different curves mimicking the shape morphing of a fish. The key design variables and constraints are defined to determine the degrees of freedom (DOFs) of the mechanism. To reduce the DOFs of the structure while possessing flexibility, two types of basic linkage units, 4-bar and 5-bar, are combined to design the final muscle mechanism that can be actuated by a single actuator. The cover is designed as passive morphing along the mechanism. The directions and placement of the scales are investigated for interference avoidance. At the end, the two designs are combined to realize a complete system with robotic scales and underlying muscle mechanism. Based on the proposed method, a prototype is built and tested to demonstrate the shape-changing capability of the proposed system through three different curved shapes.